The Phenomena of Radicalism in The Modern Era (Case Study of Higher Students) - Yessa Milianty*; Ernita Dewy Hartono; Reisa Arrifa; Lavienda William; Jason Marcellino (Universitas Syiah Kuala, 2023)
In order to find out what forms of radicalism and the driving factors for it, especially among students, is theauthor's goal to conduct this research. The research method used by the author is normative juridical research wherethe research method is a statutory approach, as for the data sources used are primary and secondary data sources.Related to the results of research conducted by the author, he stated that riots often occur in demonstrations amongstudents, this is because the demonstration is a form of radicalism whose triggering factor is the desire to carry out arebellion. In addition, this study also uncovers the fact that a social movement that was born from conditions thatprovided an opportunity for the movement; over dissatisfaction with something a social movement arises from it; thebirth of a social movement from the leadership ability of a character; The three things described by the author arefactors that trigger the emergence of radicalism among students. However, not everything is said to be radicalism ifthe act is a demonstration that ends in chaos. These acts of radicalism can basically be avoided if the authorities inthe university and government circles can carry out their obligations as well as possible. In addition, in respondingto a policy issued by the government, students should not use violences.